2009
DOI: 10.1039/b817985a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on the reaction mechanism of oxidation of primary alcohols by Zn/Cu(ii)-phenoxyl radical catalyst

Abstract: The catalytic mechanism for the oxidation of primary alcohols catalyzed by the two functional models of galactose oxidase (GOase), M(II) L (M = Cu, Zn; L = N,N'-bis(3,5-di-tert-butyl-2-hydroxyphenyl)-1-2-diiminoquinone)), has been studied by use of the density functional method B3LYP. The catalytic cycle of Cu- and Zn-catalysts consists of two parts, namely, substrate oxidation (primary alcohol oxidation) and O(2) reduction (catalyst regeneration). The catalytic mechanisms have been studied for the two reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Studies on the galactose oxidase model systems have shown a large kinetic isotope effect for the abstraction of the hydrogen atom. ,, Oxidation to the alcohol is concurrent with reduction of the copper center and is followed by the oxidation of the copper and ligand by molecular oxygen to regenerate the active catalyst. This proposed mechanism is supported by theoretical calculations …”
Section: Reactions Of Alcoholssupporting
confidence: 68%
“…Studies on the galactose oxidase model systems have shown a large kinetic isotope effect for the abstraction of the hydrogen atom. ,, Oxidation to the alcohol is concurrent with reduction of the copper center and is followed by the oxidation of the copper and ligand by molecular oxygen to regenerate the active catalyst. This proposed mechanism is supported by theoretical calculations …”
Section: Reactions Of Alcoholssupporting
confidence: 68%
“…The oxidation of primary alcohols with O 2 catalyzed by these two complexes was studied by Wu at the DFT(B3LYP) level, including solvent effects. 560 The quinone acts as a tetradentate ONNO chelating ligand and its oxygen atoms have radical phenoxyl character. In the first step of the mechanism, one of these oxygen atoms abstracts a proton from the alcohol substrate by breaking the OsH bond.…”
Section: Galactose Oxidasementioning
confidence: 99%
“…The complexes [M(L)] (M = Zn(II), Cu(II); L = N , N ′-bis(3,5-di- tert -butyl-2-hydroxyphenyl)-1,2-diiminoquinone) are functional models of galactose oxidase. The oxidation of primary alcohols with O 2 catalyzed by these two complexes was studied by Wu at the DFT(B3LYP) level, including solvent effects . The quinone acts as a tetradentate ONNO chelating ligand and its oxygen atoms have radical phenoxyl character.…”
Section: Ch Oxidationmentioning
confidence: 99%
“…A very similar role of the oxy-arms in similar Cu (II)-ONNO salen complexes was reported before. [85][86][87] In this regard, our intention was to design a tridentate Schiff base ligand with a labile pendent thioether moiety. Such a labile arm can easily leave the metal and thus creates a vacant coordination site for substrate binding during catalysis.…”
Section: Resultsmentioning
confidence: 99%